Sistem Informasi Inventori Pada CV.Tri Manunggal Berbasis Website - wirayanti, Ni Putu Eka; Sugiartawan, Putu; Suryawan, I Wayan Dharma (INFOTEKS (Information Technology, Computer and Sciences), 2020)
SMKN 1 Ende has a library as one of the facilities provided by the school to support student learning activities. The existence of a library is very important in increasing knowledge for students in schools. However, based on the results of an interview conducted with one of the librarians of SMKN 1 Ende, currently, school library data management is still using manual methods such as recording visitor member data, book data, borrowing data, and returning books in the ledger. As a result, it is inefficient and has a very big risk of mistakenly recording data on borrowing and returning books and other problems that often occur, namely when searching for data on borrowing and returning books where librarians have to reopen existing files so that it takes time. long enough. To overcome the existing problems, it is necessary to make a school library information system that will be tailored to the needs of the library. Based on the description of the problems in the library of SMKN 1 Ende, the theme that will be discussed by the researcher is